Ca(2+)-independent activation of BK(Ca) channels at negative potentials in mammalian inner hair cells - Thurm, Henrike (Blackwell Science Inc, 2005)
The defining characteristic of large-conductance Ca(2+)- and voltage-activated K(+) channels (BK(Ca)) is their allosteric activation by two distinct stimuli, membrane depolarization and cytosolic Ca(2+) ions. In this allosteric gating, increasing cytosolic Ca(2+) concentration ([Ca(2+)](i)) shifts the depolarization required for channel opening into the physiological voltage range. In fact, according to present knowledge, elevation of [Ca(2+)](i) to micromolar levels is the only means to activate BK(Ca) at membrane potentials below 0 mV. We recorded BK(Ca)-mediated currents from auditory inner hair cells (IHCs) in acutely isolated organs of Corti using the patch-clamp technique in whole-cell and excised patch configuration. In inside-out and outside-out patches, activation of BK(Ca) channels from IHCs showed the prototypic sensitivity to increased [Ca(2+)](i). However, channel activation at 0 [Ca(2+)](i) occurred at unusually negative potentials (half-maximal activation (V(h)) around 0 mV), indicating that a large fraction of the channels can be activated at physiological voltages without elevated [Ca(2+)](i). In intact IHCs, the activation curve of BK(Ca) currents recorded in whole-cell configuration exhibited a V(h) of −42 mV together with a high voltage dependence (slope factor of 10 mV) and submillisecond onset of current. Surprisingly, this activation was independent of changes in local [Ca(2+)](i) as shown by experiments that interfered with Ca(2+) influx through voltage-gated Ca(2+) (Cav) channels, release of Ca(2+) from internal stores, or intracellular buffer capacity. This behaviour is not due to β-subunits of BK(Ca) (BKβ), as genetic inactivation of the β-subunit expressed in IHCs, KCNMB1, did not affect BK(Ca) gating. We conclude that the BK(Ca) channel protein in IHCs may be modified in order to rapidly activate and deactivate at resting [Ca(2+)](i). Our results suggest that BK(Ca) may function as a purely voltage-gated K(+) channel with exceptionally rapid activation kinetics, challenging the view that both increased cytosolic Ca(2+) and depolarization are generally required for activation of BK(Ca).